Knowledge Gaps in the Pharmacokinetics of Therapeutic Proteins in Pediatric Patients - Meibohm, Bernd (Frontiers in Pharmacology, 2022)
Therapeutic proteins such as monoclonal antibodies and their derivatives, fusions proteins, hormone analogs and enzymes for replacement therapy are an ever-growing mainstay in our pharmacopoeia. While a growing number of these medications are developed for and used in younger and younger pediatric patients, knowledge gaps in the basic understanding of the molecular and physiologic processes governing the disposition of these compounds in the human body and their modulation by age and childhood development are a hindrance to the effective and timely development and clinical use of these compounds, especially in very young pediatric patient populations. This is particularly the case for the widespread lack of information on the ontogeny and age-associated expression and function of receptor systems that are involved in the molecular processes driving the pharmacokinetics of these compounds. This article briefly highlights three receptor systems as examples, the neonatal Fc receptor, the asialoglycoprotein receptor, and the mannose receptor. It furthermore provides suggestions on how these gaps should be addressed and prioritized to provide the field of pediatric clinical pharmacology the urgently needed tools for a more effective development and clinical utilization of this important class of drugs with rapidly evolving importance as cornerstone in pediatric pharmacotherapy.